Optimizing the cryopreservation and post-thaw recovery of natural killer cells is critical for the success of off-the-shelf platforms - Saultz, Jennifer N.; Otegbeye, Folashade (Frontiers in Immunology, 2023)
Natural killer (NK) cells are a promising allogeneic, off-the-shelf, cellular immunotherapy product. These cells can be manipulated ex vivo, genetically edited to enhance tumor targeting and expanded to produce large cell banks for multiple patient infusions. Therapeutic efficacy of these products depends on the recovery of viable and functional cells post-thaw. Post-thaw loss of viability and cytolytic activity results in large, and often variable, discrepancies between the intended cell dose (based on counts at cryopreservation) and the actual dose administered. Compared to their highly activated state in fresh culture, post-thaw NK cells demonstrate critical changes in cytokine production, cytotoxic activity, in vivo proliferation and migration. When these NK cells are introduced into the highly immunosuppressive tumor microenvironment, the functional changes induced by cryopreservation further limits the clinical potential of these products. This report will review the impact of cryopreservation on ex vivo expanded NK cells and outlines strategies described in published studies to recover post-thaw function.